Hakikat Pendidik Menurut Hadis Nabi - Isropil Siregar (Khazanah : Journal of Islamic Studies, 2022)
The position of educators according to Islam is noble because they are the successors of the Prophet's task in conveying knowledge based on the Al-Quran and As-Sunnah. Therefore, educators are obliged to form noble personalities and have commendable traits as desired by Islam because educators are qudwah and also good uswah for students